Pendidikan Akhlak Menurut Ibn Miskawaih dan Relevansinya terhadap Pendidikan Karakter Bangsa - Semin Semin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2019)
The extraordinary development and explosion of science and information technology should also be accompanied by attention to education, especially moral education so that character education has lately been echoed as forming emotional intelligence of individuals, especially in the world of education being able to become a shield to be able to survive in the face of challenges of the times. Along with these problems Ibn Miskawaih in the book